CRITICAL APPRAISAL OF EFFECTIVENESS OF ORAL FINGOLIMOD ON RELAPSING MULTIPLE SCLEROSIS - Rizaldy Taslim Pinzon; Rosa De Lima Renita Sanyasi (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2017)
Oral fingolimod has been recently accepted as a treatment for relapsing Multiple Sclerosis (MS) by the Indonesian Food and Drug Administration. The number of MS patients is increasing in Indonesia. There is a critical need of systematically reviewing the new medication for both efficacy and safety. This review aimed to appraise the clinical evidences of oral fingolimod for the effective treatment of relapsing MS. We searched in Pubmed database. We limited our search to only articles that were in full text, published within the last 10 years, and in English. We used the Jadad scale to measure the quality of the evidences. We only found 3 trials, all conducted with randomized and double blind design. The three trials were: the FREEDOMS I, FREEDOMS II, and TRANSFORMS studies. The FREEDOMS studies compared with placebo, and the TRANSFORMS study compared with injectable interferon. All of the studies have good quality in methodology (Jadad scale 3). The results of the three studies showed the benefit of oral fingolimod in reducing MS relapse compared with placebo with relative risk reduction range from 48% to 54%, and also in reducing new lesions in T2 brain MRI with relative risk reduction range from 35% to 74%. Our critical appraisal found that oral fingolimod improved clinical outcomes. The availability of oral fingolimod in Indonesia makes it one of the options in treatment of MS relapse in Indonesia and has been demonstrated to be effective and safe with relatively small risk.